Penerapan Sistem Smart Building pada Pusat Perbelanjaan Kebutuhan Pernikahan di Kota Makassar - Chaerunnufus Chaerunnufus; Juhana Said; Muhammad Zaki (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
This research discusses the design of a wedding essentials shopping center in the city of Makassar with the application of a Smart Building system to enhance operational efficiency, security, and visitor comfort. The Smart Building concept is applied to lighting, ventilation, security, and energy management systems through the integration of sensor technology, automation, and Building Management System (BMS). The research methods include primary data collection through field observations and interviews, as well as secondary data from literature and city planning documents. The analysis focuses on space requirements, activity patterns, and the potential for technology integration. The research findings indicate that the implementation of Smart Building can optimize energy use, facilitate facility management, and create a more comfortable and safe shopping environment. The final design includes efficient spatial zoning, sensor-based utility management, as well as security systems and information services that are digitally connected. This concept is expected to serve as a model for the development of themed shopping centers in other cities with wedding industry potential.